Nursing Documentation of Postoperative Pain Management: A Documentary Analysis. Issue 3 (July 2019) - Shoqirat, Noordeen; Mahasneh, Deema; Dardas, Latefa; Singh, Charleen; Khresheh, Reham
Abstract : Background: Although proper documentation of pain for postoperative patients is essential to promote patient health outcomes, there is limited examination of nurses' documentation of pain management. Purpose: The purpose of this study was to qualitatively analyze nursing documentation of pain management among postoperative patients in Jordan. Method: A documentary analysis method was used. A purposive sample of 80 medical records were reviewed, and a total of 720 nursing records were analyzed. Results: The analysis revealed that nurses' documentation of pain management was limited, vague, incomplete, and largely dependent on their subjective evaluation. Many of the documented goals were broad, not specific, not measurable, and with no time frame. Conclusions: Documentation patterns revealed a lack of proactive and systematic approach to pain assessment and management. Furthermore, there was little documented evidence of efforts to evaluate the effectiveness of pain management interventions. Findings have important implications for standardizing documentation of pain assessment, intervention, and evaluation.